Analisis Kesehatan Dan Keselamatan di Lingkungan Kerja Proyek Pembangunan Sumatera Utara: Studi Kasus PT Indomaret - Keyla Harista Nasution; Maulidya Permata; Abdurrozaq Hasibuan (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
This research investigates safety and health in the work environment of development projects in North Sumatra with a focus on PT Indomaret as a case study. The research method used involves a qualitative approach and literature analysis. Through in-depth interviews and field observations, key challenges were identified including lack of awareness and compliance with work safety procedures as well as the need for skills training. Environmental and technical factors, such as weather conditions and the selection of equipment that meets safety standards, also influence the level of risk. However, effective safety management practices, such as regular meetings and periodic inspections, were also found. The implications of this research emphasize the importance of increasing awareness, selecting appropriate equipment, and effective management practices to create a safe and healthy work environment. Recommendations include implementing regular training, careful risk evaluation, and maintaining effective management practices. This research provides valuable insights for practitioners and researchers in efforts to improve safety and health in the work environment of development projects in North Sumatra.